Effectiveness of Online Learning Through Google Class Room to Interests And Learning Outcomes of Gadar Maternal and Neonatal Courses In Students Semester 4 STIKES Dian Husada Mojokerto - Titiek Idayanti; Widya Anggraeni; Vera Virgia; Kurnia Indriyanti Purnamasari (Universitas Islam Lamongan, 2021)
The world of education is one of the many sectors affected by the covid-19 pandemic. The existence of this pandemic, requires all education from the elementary level to college to be able to continue to carry out learning even though not through face-to-face, but in a different way, namely by online or often referred to as online (learning online). This research aims to find out the influence of online learning through google class room on the interests and learning outcomes of MATERNAL & neonatal GADAR courses in students of semester 4 of STIKes Dian Husada Mojokerto. The method used in this study was a pre-experiment with the design of one group pre-test-post-test. This research sample was a 4th semester student of STIKes Dian Husada Mojokerto who numbered 26 students. The results showed that there was an influence before and after being given treatment using online learning through google classroom on the interests and learning outcomes of maternal &neonatal gadar courses. The conclusion of the results of the study, that google class room is less effective is used in online learning for maternal &neonatal courses, because for learning the course requires a more effective practicum if done face-to-face (offline).Keyword : Online Learnin, Interests And Learning Outcomes